INTERVENTIONAL CORRECTION OF EXTRAHEPATIC PORTAL HYPERTENSION IN PATIENT AFTER LIVER TRANSPLANT. THE FIRST CASE REPORT IN UZBEKISTAN - Konstantin Semash; Timur Djanbekov; Mirshavkat Akbarov; Azim Usmonov; Maksudjon Shermatov; Temurbek Gaybullaev (Central Asian Journal of Medicine, 2023)
Liver transplantation is a multi-component and complex type of operative treatment. Patients undergoing such a treatment sometimes are getting various complications. One of these complications is a portal hypertension associated with portal vein stenosis. Materials and methods. In 8 months after the right lobe transplantation from living donor in an adult patient the signs of portal hypertension were observed. Stenosis of the portal vein was revealed. Due to this fact percutaneous transhepatic correction of portal vein stenosis was per formed. Results. As a result of the correction of portal blood flow no more portal vein stenosis obtained. According to the laboratory and instrumental methods of examination the graft had a normal function, portal blood flow was adequate. In order to control the anastomosis patency Doppler ultrasound was performed in the 5-days and 21-days period. Due to these examinations the no stenosis was obtained, the rate of blood flow in the portal vein due to Doppler data has reached 60-70 cm/sec, and a decrease of the spleen size was noted.